High-throughput genotyping of advanced congenic lines by high resolution melting analysis for identification of Bbaa2, a QTL controlling Lyme arthritis. (March 2012) - Bramwell, Kenneth K.C.; Ma, Ying; Weis, John H.; Teuscher, Cory; Weis, Janis J.
Congenic mapping is a powerful strategy to identify genomic loci regulating quantitative traits. Generating congenic lines is an iterative process of refinement that is both time and resource intensive. Here we report an alternative to traditional microsatellite marker analysis or costly high-density oligonucleotide single nucleotide polymorphism (SNP) arrays for congenic genotyping. The identification of inherited SNP variability in congenic lines using high resolution melting analysis (HRMA) represents a novel application of the method. The blocked probe HRMA approach offers a scalable, low cost, closed-tube system that benefits from rapid turnaround times, and unequivocal interpretation. The markedly higher prevalence of SNPs relative to microsatellites in the genome allows much greater flexibility for the identification of new genotyping landmarks as congenic intervals are refined. We have adopted this approach in our development of B6.C3-Bbaa2 congenic lines for the identification of loci regulating murine Lyme arthritis severity. As a result, we have been able to fully genotype individuals prior to weaning age, and expand our number of breeding cages without increasing our colony budget. Thus far, 26 SNP markers have been successfully mapped to the Bbaa2 locus. This has facilitated the identification of 20 novel B6.C3-Bbaa2 congenic lines spanning the original interval.